Effects BNT compound incorporated on structure and electrical properties of PZT ceramic - P. Jaita (2018)
Ferroelectric ceramics with formula Pb(Zr0.52Ti0.48)O3/x(Bi0.5Na0.5)TiO3(when x = 0, 0.1, 0.5, 1.0 and 3.0 wt%) were prepared by a solid-state mixed-oxide method and sintered at the temperature between 1050 and 1200 °C for 2 h to obtain dense ceramics. It was found that the optimum sintering temperature was 1200 °C at which all the samples had relative density at least 96% of their theoretical values. Phase analysis using X-ray diffraction showed tetragonal and rhombohedral perovskite structure of PZT with no BNT peak detected, indicating that completed solid solutions occurred for all compositions. Scanning electron micrographs of fractured PZT/BNT ceramics showed equiaxed grain shape with mixed-mode of transgranular and intergranular fractures. Addition of BNT significantly decreased grain size of the PZT ceramic. Measurement of room temperature dielectric constant indicated a gradual increase with increasing BNT content. Results of ferroelectric characterization showed a slight decrease of remanent polarization and coercive field for BNT-added samples, suggesting ceramics which could be easily poled. Good piezoelectric coefficient (d33) could be maintained and comparable to that of pure PZT ceramic for the sample with 1.0 wt% BNT addition. © 2011 Elsevier B.V. All rights reserved.